Interference and economic damage threshold of smooth pigweed in soybean - Serleni Geni Sossmeier; Mateus Possebon Bortoluzzi; Mauro Antônio Rizzardi (Pesquisa Agropecuária Brasileira)
Abstract The objective of this work was to determine the interference and economic damage threshold of smooth pigweed (Amaranthus hybridus) in soybean. The experiments were carried out in two agricultural harvests (2020/2021 and 2021/2022) in an area with natural infestation of smooth pigweed. The treatments consisted of different levels of smooth pigweed infestation (0, 1, 3, 6, 9, and 12 plants per square meter) in an area cultivated with soybean. The design was completely randomized with ten replicates. The analyzed variables were: number of pods per plant; grains per pod; and soybean grain yield, converted into loss percentage in relation to the controls without the presence of smooth pigweed. One smooth pigweed plant per square meter can reduce soybean yield, on average, by 4.32 to 5.09%, whereas the presence of 12 plants per square meter reduces soybean yield by 36.03 to 37.93%. The economic damage threshold of smooth pigweed in soybean occurs in the range of 0.35 to 0.93 plants per square meter. When the cost of control is lower, the economic damage threshold is achieved with smaller infestations of 0.36 plants per square meter. However, when the cost of control is high, the economic damage threshold becomes economically viable with larger infestations above 0.63 plants per square meter.